Prescribing patterns and determinants for elderly patients with Parkinson's disease in Japan: a retrospective observational study using insurance claims databases - Seki, Morinobu; Kawata, Yayoi; Hayashi, Ayako; Arai, Masaki; Fujimoto, Shinji (Frontiers in Neurology, 2023)
Background This study aimed to determine real-world prescribing patterns and determinants for Japanese patients with Parkinson's disease (PD), with a focus on patients ≥75 years. Methods This was a retrospective, observational, longitudinal study of patients with PD (≥30 years, ICD-10: G20 excluding Parkinson's syndrome) from three Japanese nationwide healthcare claim databases. Prescription drugs were tabulated using database receipt codes. Changes in treatment patterns were analyzed using network analysis. Factors associated with prescribing patterns and prescription duration were analyzed using multivariable analysis. Results Of 18 million insured people, 39,731 patients were eligible for inclusion (≥75-year group: 29,130; <75-year group: 10,601). PD prevalence was 1.21/100 people ≥75 years. Levodopa was the most commonly prescribed anti-PD drug (total: 85.4%; ≥75 years: 88.3%). Network analysis of prescribing patterns showed that most elderly patients switched from levodopa monotherapy to adjunct prescription patterns, as did younger patients, but with less complexity. Elderly patients who newly initiated PD treatment remained on levodopa monotherapy longer than younger patients; factors significantly associated with levodopa prescriptions were older age and cognitive impairment. Commonly prescribed adjunct therapies were monoamine oxidase type B inhibitors, non-ergot dopamine agonists, and zonisamide, regardless of age. Droxidopa and amantadine were prescribed as adjunct levodopa therapy slightly more frequently among elderly patients; levodopa adjunct therapy was prescribed when the levodopa dose was 300 mg, regardless of age. Conclusion Prescribing patterns for patients ≥75 years were levodopa centered and less complex than for those <75 years. Factors significantly associated with levodopa monotherapy and continued use of levodopa were older age and cognitive disorder. Clinical trial registration UMIN Clinical Trials Registry, https://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000053425 (UMIN000046823).